2018
DOI: 10.1016/j.jacc.2018.04.085
|View full text |Cite
|
Sign up to set email alerts
|

The Long Noncoding RNA CAREL Controls Cardiac Regeneration

Abstract: LncRNA CAREL regulates cardiomyocyte proliferation and heart regeneration in postnatal and adult heart after injury by acting as a competing endogenous ribonucleic acid on miR-296 that targets Trp53inp1 and Itm2a.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
88
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(91 citation statements)
references
References 25 publications
2
88
0
1
Order By: Relevance
“…For example, Micheletti et al showed that lncRNA Wisper could reduce the pathological development of cardiac fibrosis in response to MI and prevent adverse remodeling in the damaged heart [10]. Cai et al found that lncRNA CAREL regulated cardiomyocyte proliferation and heart regeneration in postnatal and adult heart after injury by miR-296/Trp53inp1/ Itm2a axis [11]. Recently, Hu et al reported that lncRNA MALAT1 inhibition attenuated acute MI through miR-320-Pten axis [12].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Micheletti et al showed that lncRNA Wisper could reduce the pathological development of cardiac fibrosis in response to MI and prevent adverse remodeling in the damaged heart [10]. Cai et al found that lncRNA CAREL regulated cardiomyocyte proliferation and heart regeneration in postnatal and adult heart after injury by miR-296/Trp53inp1/ Itm2a axis [11]. Recently, Hu et al reported that lncRNA MALAT1 inhibition attenuated acute MI through miR-320-Pten axis [12].…”
Section: Introductionmentioning
confidence: 99%
“…Several lncRNAs have been reported to have roles in regulating heart development and function. For example, depletion of Chast/Wisper and overexpression of Mhrt, Tincr or Carel protected the heart from hypertrophy in response to pressure overload following transverse aortic constriction surgery (Cai et al, 2018;Han et al, 2014b;Micheletti et al, 2017;Shao et al, 2017;Viereck et al, 2016). Inhibition of Fendrr led to embryonic lethality around E13.5 with cardiac hypoplasia (Grote et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs are distributed in both the nucleus and cytoplasm and regulate intracellular signaling pathways via different mechanisms, including chromatin modification, gene transcription regulation, and competing endogenous RNAs (ceRNAs) [48]. Among these, ceRNAs have a potentially important role in cardiac-related diseases [49,50]. Recent studies revealed that cardiac hypertrophy-related factor regulated cardiac hypertrophy by targeting miR-489.…”
Section: Discussionmentioning
confidence: 99%